Dental Caries in a Cohort of Very Young American Indian Children - Warren, John J. (2012)
OBJECTIVES: This paper reports the prevalence and severity of caries in a group of 16-month-old American Indian children. METHODS: The study is an ongoing longitudinal study of risk factors for caries in children from a Northern Plains Tribal community. Children were examined for caries and risk factor data collected at approximately 1, 4, 8, 12 and 16 months of age. Surface-specific caries data were collected and the presence of pre-cavitated “white spot” lesions was recorded at the subject level. RESULTS: The mean age was 15.4 months for the sample of 232 children. Caries prevalence was 31.9%, while an additional 29.3% had white spot lesions only. Mean dmfs was 1.57, and ranged from 0 to 44 surfaces. Nearly 3% of all erupted tooth surfaces were affected and maxillary central incisors had the highest prevalence of caries (22%). CONCLUSIONS: Among the very youngest children, dental caries prevalence was very high among these American Indian children.